Performance Differences between Men and Women Elite Athletes in Biathlon, in Pursuit Contest - Bletsou, Ελευθερία; Gerodimos, Βασίλειος; Pollatou, Ελιζάνα (Inquiries in Physical Education and Sport, 2006)
Biathlon is an Olympic sport, officially recognized by the Greek Ski Federation. It is a particularly technical sport as it is consisted from two complex activities, ski cross country and rifle shooting. The present study examined the pursuit contest which combines shooting accuracy and skiing performance. The aim was to investigate: a. the effect of gender in several factors that affect shooting, b. the modification of shooting factors during contest and c. the effect of gender in final performance. Supplementary, to present also, indicative values of young biathlon athletes. One hundred sixteen (n=116) biathlon elite athletes participated in the study, aged 19-20 years old, fifty nine of those (n=59) were women and fifty seven (n=57) were men. For the statistical analysis a two way analysis of variance (two way ANOVA) with repeated measures and an Independent Samples t-test was used. The results revealed that gender did not affect statistically significant none of the variables during shooting procedure (accuracy, meantime among shots and shooting preparation time) in prone and upstanding position. Also there was no modification of the above variables during the contest. In contrast, gender affected statistically significant (p< .05) the final performance in pursuit contest. It can be concluded that performance differences between men and women were due to skiing performance and not to the demanded shooting abilities (accuracy, meantime among shots, shooting preparation time) which seem to be equally developed between men and women biathlon elite athletes.